Diseminasi Pembelajaran Kreatif Menggunakan Media Mobile Gamification Learning System (MGLS) - Sulaksono, Aulia Sanova; Yusnaidar, Yusnaidar; Afrida, Afrida; Asmiyunda, Asmiyunda; Hasibuan , M Haris Effendi (Fakultas Sains dan Teknologi, Universitas Jambi, 2024)
The learning phenomenon in the era of the industrial revolution 5.0 based on mobile digital is being loved and is in great demand by the current generation of digital natives, namely incorporating mobile cycle game elements on smartphone devices, this mode is called the Mobile Gamification Learning System, considering that the current generation of students have learning styles that tend to be active visually, kinesthetic, sequential and sensing. However, the term gamification itself still sounds foreign to some teachers at SMA Negeri 6 Kerinci and has never applied it in class, considering the limited knowledge of teachers in using ICT. Seeing these conditions and situations, it is necessary to carry out dissemination activities on the use of gamification application tools in order to advance the quality of education through developing teacher competence in applying technology-based science. The results of this dissemination activity have had a very good effect on teachers' basic knowledge and skills in utilizing gamification media and creating an active, creative, fun and motivating classroom atmosphere for student learning.